Commentary: Scoring Flaw in the Persian Version of Knee Injury and Osteoarthritis Outcome Score: A comment on “Validation of a Persian-version of Knee injury and Osteoarthritis Outcome Score (KOOS) in Iranians with knee injuries. Osteoarthritis Cartilage 2008 Oct;16(10):1178-82” - Zahra Sadat Rezaeian (مجله پژوهش در علوم توانبخشی, 2021)
Knee Injury and Osteoarthritis Outcome Score (KOOS) assesses aspects of knee-related complications in young and middle-aged individuals suffering from various knee injuries. Salavati et al. cross-culturally adapted KOOS into Persian. However, the answer options for the fourth and fifth questions in the symptom section of the Persian version are ordered in reverse. Since there was not any scoring guide for Persian users that pointed out this issue, in spite of the fact that the correction is now accepted and cited by http://www.koos.nu, I decided to publish this commentary in Journal of Research in Rehabilitation Sciences as one of the highly cited bilingual journals in Iran. Considering this correction will definitely make the researches involving the Persian-speaking population more accurate and valid.